MULTICULTURAL EDUCATION AND INTERRELIGIOUS LEADERS KNOWLEDGE - Marjuni, A. (Al-Ulum, 2014)
Multicultural-education is meant to portray about the efforts that must be carried out by teachers and lecturers in the midst of a growing cultural diversity in todays society. Teachers and lecturers are expected to contribute in revising the learning material as well as to reform the learning system with wider insight in the globalization process. The birth of various teachings or understandings which are not relevant with religious values, such as secularism and materialism, tends to make religion education to be helpless and even to make religion to be ruled out in various fields. This may also hit people when religion does no longer function effectively in multidimensional and multicultural life.Â ----------Pendidikan berbasis multikultural dimaksudkan untuk menggambarkan tentang upaya-upaya yang harus dilakukan oleh guru dan dosen di tengah-tengah keanekaragaman budaya yang berkembang dalam masyarakat saat ini. Guru dan dosen diharapkan dapat berkonstribusi dalam merevisi materi pembelajaran serta melakukan reformasi dalam sistem pembelajaran dengan wawasan yang lebih luas dalam arus globalisasi. Lahirnya berbagai ajaran atau pemahaman yang tidak relevan dengan nilai-nilai agama, seperti aliran materialis dan sekuler, maka ada kecenderungan membuat pendidikan keagamaan menjadi tidak berdaya dan lebih lagi jika agama telah dikesampingkan dalam berbagai bidang. Hal ini mungkin juga menerpa umat bila agama tidak lagi berfungsi secara efektif dalam kehidupan multidimensi dan multikultural.